Development Of Audio-Visual Learning Media to Introduce Healthy Living (Cleanliness) Early Childhood 5-6 Years Old Kindergarten Kundur Barat, Riau Islands (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
This research aims to develop audio-visual learning media to introduce healthy living behaviors (cleanliness) in early childhood. The method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects involved media experts, material experts, teachers, and children aged 5–6 years at Ummul Quro Kindergarten, West Kundur, Riau Islands. Data was collected through questionnaires, observations, and documentation, then analyzed using the Likert scale based on validation, practicality, and effectiveness results. The validation results of media experts obtained a percentage of 76% and material experts 78% with an average of 77% (feasible category). The teacher's practicality test obtained 77.1% (feasible), the children's limited effectiveness test 86%, and the broad effectiveness test 89% (effective category) with a total of 84%. The results of the implementation show that there is an increase in children's understanding of clean and healthy living behaviors. Thus, the audio-visual learning media developed is declared feasible, practical, and effective for use in early childhood learning